2D and 3D thermoelastic phenomena in double wall transpiration cooling systems for gas turbine blades and hypersonic flight - Skamniotis, C; Cocks, A (Elsevier, 2021)
Double wall transpiration cooling (DWTC) systems allow the operating temperature of gas turbines to be increased above current levels using conventional cooling technologies, promising further enhancements in engine efficiency and a reduction in fuel consumption and emissions. Alongside the outstanding cooling performance of DWTC systems, there are structural integrity implications which have not been fully evaluated. Theoretical and Finite Element (FE) analyses presented here evaluate thermal stresses arising in a range of double wall configurations in two-dimensional (2D) and three-dimensional (3D) space. Geometric effects of wall spacing, wall thickness ratio, connecting pedestal spacing between the walls and pedestal thickness, are found to have a similar effect on the stress state in both the 2D and 3D models, and are highly sensitive to the underlying structural constraints. Although an inner cool wall may be essential for applying internal impingement cooling in the system to enhance its aerothermal performance, at the same time the inner wall increases compression in the hot outer wall, due to the kinematic constraint that the two walls must extend equally. As a result, the critical compressive stresses in the hot wall can be relieved by using a thinner inner wall. Our study determines the essential nominal stress fields that drive stress concentrations and associated local creep-plasticity-fatigue effects at critical features in DWTC systems, such as effusion holes and pedestals.